Blockchain-enabled bioacoustics signal authentication for cloud-based electronic medical records. (April 2023) - Mohammed, Zainulabedin Hasan; Chankaew, Keattisak; Vallabhuni, Rajeev Ratna; Sonawane, Vijay R.; Ambala, Srinivas; S, Markkandan
Abstract: In this paper, we explore Blockchain technology can be used to build a reliable decentralised authentication system. High security for the bioacoustics signal authentication mechanism is guaranteed by using an optimised number of secured features from the bioacoustics signal rather than conventional biometric features for authentication, and by utilising a blockchain model to improve the robustness of multiple checks on the data. It allows for trustworthy authentication and the tracking of terminal activity. Then, light weighted cryptography (LWC) is developed to offer protection at each edge node and terminal. Finally, the belief propagation (BP) algorithm for retraining the features of the bioacoustics signal serves as the foundation for the catching method. It improves hit ratio while decreasing delay time. The experimental setup uses the bioacoustics signals for authentication instead of conventional biometric features, and the use of a blockchain model for data transparency improves the efficiency of multiple checks. When this happens, privacy and safety are both boosted.